Physical activity patterns in Mozambique: urban/rural differences during epidemiological transition. - Padrão, Patrícia (2012)
Abstract: Objective. To assess the socio-demographic determinants of physical activity, by intensity and domain, across urban and rural areas in Mozambican adults. Method. A national representative sample (n = 3323) of subjects aged 25-64 years was evaluated in 2005 following the World Health Organization (WHO) Stepwise Approach to Chronic Disease Risk Factor Surveillance (STEPS), which includes the Global Physical Activity Questionnaire. We computed prevalences, and age- and education-adjusted prevalence ratios (PR), with 95% confidence intervals (95%CI). Results. Most of the Mozambicans reported a high physical activity level, according to the WHO criteria (urban women: 83.2%, 95%CI 77.4, 89.0; rural women: 93.2%, 95%CI 89.0, 97.3; urban men: 78.9%, 95%CI 74.7, 83.1; rural men: 91.6%, 95%CI 85.5, 97.6). The prevalences of < 75 min/week of vigorous activities were higher in urban settings (women: PR=2.21; men: PR=2.28) and increased with education, regardless of place of residence (PR ranging between 1.75 and 5.72 for more vs. less educated subjects). Work activities were the most important contributor to the overall physical activity, followed by transport. Conclusion. Most of the Mozambicans reported to be physically active. Vigorous activities were less common in urban areas and among the more educated subjects, depicting an ongoing shift to more sedentary behaviours in this setting. (C) 2012 Elsevier Inc. All rights reserved.